Status iodium pada anak usia sekolah berdasarkan ekskresi iodium urin dan asupan iodium - Widya Ayu Kurnia Putri; Dodik Briawan; Hidayat Syarief; Leily Amelia (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2019)
Iodine status in school-age children determined from iodine urine excretion and iodine intakeBackground: School-age children are more at risk if they experience deficiencies and excess iodine. The concentration of iodine in urine is a good biomarker for assessing iodine intake, 90% of iodine intake will be excreted through urine. Objective: This study aimed to analyze the iodine status of school-age children based on urinary iodine excretion (UIE) and iodine intake.Method: The study design used a cross-sectional study on 44 healthy school-aged children in Bogor Regency. Subject selection was done purposively in healthy 5th-grade elementary school students. The data taken in this study was urine iodine excretion concentration and food recall (1x24 hours). Data were analyzed using descriptive analysis and Pearson correlation test.Results: Median iodine excretion concentration in urine was 157 μg/l and the average daily iodine intake of children was 83.29 mg/day. Conclusion: The concentration of iodine excretion in the urine of the children is in the category of sufficient iodine as recommended by WHO / UNICEF / ICCID while the daily intake of iodine for children is still in the less category. The results showed that there was no association of iodine daily intake with iodine excretion concentration in urine(p=0.469).